Odpowiedź:
a) 2a + (3a-7)= 2a +3a -7= 5a -7
b) ( 2x-3) +x= 2x-3 +x= 3x-3
c) 7- (5x+4)= 7 - 5x -4= 3-5x
d) 3x - ( y-2x)= 3x -y +2x= 5x-y
e) - ( 3a+6 ) -4= -3a -6 -4= -3a - 10
f) - ( x -2y ) -3x= -x +2y -3x= -4x +2y
g) ( 2p -1) +( 3+5p)= 2p - 1 +3 +5p= 7p +2
h) ( 4-2x) - (7x -2)= 4 - 2x -7x +2 = 6 -9x
i) - ( 2x -1) + ( 3x+1)= -2x +1 +3x +1= x +2
j) ( 2m + 4n) + ( m- 0,5n)= 2m +4n +m -0,5n= 3m +3,5 n
k) ( 4a - 7 b ) - ( 2a+3b)= 4a - 7 b -2a -3b= 2a -10b
l) - ( 2p-r) - ( 2r -p)= -2p +r -2r +p= -p -r
Szczegółowe wyjaśnienie: